MNOC'S LEVEL OF ENGAGEMENT WITH HUMAN RIGHTS OBLIGATIONS IN TRANSNATIONAL LITIGATIONS FROM THE NIGER DELTA: Received: 15th April 2021; Revised: 04th July 2021, 23rd July 2021; Accepted: 26th October 2021 - Ochei, Nkem Violet; Ezeani, Elimma; Anderson, Craig (PEOPLE: International Journal of Social Sciences, 2021)
The approach that Multinational Oil companies (MNOCs) use to comply with their human rights obligations translates to the different levels of engagement with stakeholders. For example, concerns regarding alleged human rights and environmental violations of MNOCs usually start with a notification, and then a formal complaint and if this is handled improperly will result in litigation. The ways MNOCs handle the disputes reflects whether the company pursues an inactive, reactive, active or proactive level of engagement with its human right obligations. This paper evaluates each level of engagement against a selected set of transnational human rights and environmental litigations arising from the Niger Delta. This evaluation reveals that MNOCs with a proactive approach considers the engagement and implementation of their human right obligations as a shared societal responsibility and are more inclined to look at the background of the complaint to solve the underlying problems in collaboration with all stakeholders. This paper, therefore, concludes that a proactive approach will lead to an improvement in human rights and environmental protection, in partnerships with local governments, local communities, and NGOs.